The Effectiveness of Blended Learning Implementation in Ecological Chapters Judging from the Understanding of Students' Concepts - Pitaloka, Elok Dyah; Suyanto, Slamet (FMIPA UNNES, 2019)
The use of technology in the process of learning activities can create a new atmosphere in biology learning, namely direct learning and learning using quipper school online. Learning like this is known as blended learning. The class used for the study was taken through cluster random sampling technique namely X MIPA 2 (experimental class) which implements blended learning and X MIPA 3 (control class) which implements a scientific approach. The implementation of blended learning on the topic of ecology is expected to be effective towards understanding concepts. Blended learning is effective on understanding concepts in ecological discussion because they fulfill three indicators, namely: (1) the average posttest of the experimental class 74.95> the mean posttest of the control class is 64.98, (2) The value of understanding the concepts to the two classes shows a significant difference with the values significance of 0,000<0,05, (3) Mean value of N-Gain experimental class 0.52> N-Gain mean value of control class 0.32. Thus, the implementation of blended learning in the ecology chapter in terms of understanding the concept is said to be effective.